السبیل و مرکزیته في المعجم الأخلاقي القرآني - مشکین فام, بتول (Al-Adab Journal, 2018)
There are key terms in the Holy Quran, centering around a focused word in a complicated semantic field within a comprehensive conceptual system. These focused words and key terms play a significant role in establishing the conceptual structure of a Quranic view. The present study aims to recognize these words, extract them from the Quran lexicon and draw attentions to the interlocking relations which govern these semantic fields. This would help to lay a stable foundation for literary analysis as it will be described later in this paper. Accordingly this research presents the following issues:Recognizing the Quranic terms which make up the semantic field of “route,” i.e., “maslak,” in either a metaphorical or real sense. This can equally function in religious and non-religious fields including:The route meaning in generalShari’ah and its stable approachWhat is contradictory to religionChallenging the central point view in the moral conceptual system devised by the Japanese orientalist, Toshihiko Izutsu in his books: “Allah and Man in the Quran” and “Ethico-Religious Beliefs in Islamic Theology.”Developing a proposal to change Izutsu’s idea through the following suggestions:That the word “sabil” substitutes “kufr” as the focused word;That the field words around sabil have the following semantic features:Positive (as used in sirat or sabil) in statements and definitions with a positive connotation, such as “accepting guidance” and “advancement.”Negative when the guidance to the sabil is missing which itself leads to:Retraction, aberration and deviationExodus, revolt and rebellionApostasy and retrogradationThat the moral conceptual system comprises three types which are respectively concerned with describing the status of man in relation to his God, to himself and to other people in the society.